Tale of spontaneous passage of large proximal ureteric calculus in a male patient - Agrawal, Shivendra; Srinath, N.; Prathvi (International Journal of Research in Medical Sciences, 2023)
Ureteric stones are very notorious. Sometimes a very small stone may require a surgical removal and sometimes a large stone might pass spontaneously. We report a case of a 43 years old male patient who presented to our department with complaint of right flank pain of 1-week duration. This patient was diagnosed with right proximal ureteric calculus (11×6 mm) at L3 level. He was planned for ureterorenoscopy lithotripsy (URSL)/push back percutaneous nephrolithotomy (PCNL). Patient needed time for getting financially prepared for the surgery. Meanwhile we prescribed him an alpha blocker once daily at bedtime, oral analgesia SOS and advised to take adequate hydration. On 10th day of first presentation, to our surprise, the patient came with a stone in his hand, which he has passed spontaneously, and was confirmed by a radiograph. The likelihood of a ureteric stone spontaneously passing during expectant treatment is influenced by various factors, including its size, location, and orientation within the ureter. 11×6 mm proximal ureteric stone is the largest stone passed spontaneously in a male patient in our institute and most probably in literature.